IMPLEMENTATION OF COOPERATIVE EXPERIENTIAL LEARNING MODEL BASED ON SOFT SKILL AND HARD SKILL IN IMPROVING THE LEARNING COMPETENCY IN LKP YUWITA BEAUTY COURSE IN TASIKMALAYA CITY - Wiwin Herwina; Lilis Karwati; Ahmad Hamdan; Cucu Hidayat; Cucu Hidayat (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This research is based on the problem of how to implement cooperative learning experiential learning model based on soft skill and hard skill in improving the competence of studying citizen in beauty course of LKP Yuwita in Tasikmalaya City. Theories underlying this research are the theory of out-of-school education, learning models, integrated learning, citizens’ learning competencies, and beauty course institutions. The approach used in this research is qualitative approach and research & development (R & D) approach. The research method used is description and experiment method. The result of the research shows that the implementation of cooperative experiential learning model based on soft skill and hard skill can strengthen the concept of cooperative experiential learning development based on soft skill and hard skill, including: clarity of learning objectives, learning materials, methods, media, and evaluation of learning that gives opportunity for the citizens to be creative through cooperation among the villagers and tutors as facilitators whose results contribute to the improvement of the learning system that became the foundation in the development of cooperative experiential learning model based on soft skills and hard skills.